Diagnostic yield of liquid‐based cytology in serial pancreatic juice aspiration cytological examination. Issue 1 (25th October 2022) - Kitagawa, Koh; Mitoro, Akira; Tomooka, Fumimasa; Asada, Shohei; Fujinaga, Yukihisa; Nishimura, Norihisa; Kaji, Kosuke; Kawaratani, Hideto; Akahane, Takemi; Ozutsumi, Takahiro; Kaneko, Miki; Fujimoto, Yuki; et al.
Abstract: Objectives: Serial pancreatic juice aspiration cytological examination (SPACE) via endoscopic retrograde cholangiopancreatography is a useful diagnostic method for early‐stage pancreatic cancer, such as carcinoma in situ that are difficult to diagnose by endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA). However, the diagnostic accuracy of SPACE is low, which is attributed to problems regarding specimen treatment. Hence, we evaluated the diagnostic efficacy of liquid‐based cytology (LBC) in pancreatic juice cytology for pancreatic cancer. Methods: We retrospectively analyzed 24 patients with suspected pancreatic cancer that was difficult to diagnose by endoscopic ultrasound‐guided fine needle aspiration who underwent SPACE using LBC between April 2017 and April 2021. Results: The most common reason for performing SPACE was localized stenosis of the main pancreatic duct without a mass. Eleven patients were diagnosed with malignancy after surgical resection, nine of whom had pancreatic ductal adenocarcinoma. Ten patients were diagnosed as benign after a follow‐up of more than 1 year. The nine cases of malignancy were diagnosed before surgical resection by SPACE using LBC, with a sensitivity of 81.8% and specificity of 100%. The overall diagnostic accuracy was 91.7%. A total of 152 LBC examinations were performed via SPACE, with an adequate sample collection rate of 88.9%. No adverse events, including acute pancreatitis, occurred after endoscopic retrograde cholangiopancreatography. Conclusion: SPACE with LBC offers good diagnostic efficacy in patients with pancreatic cancer that is difficult to diagnose by endoscopic ultrasound‐guided fine needle aspiration.